SIMULATION OF POLLUTION LOAD CAPACITY USING QUAL2Kw IN BABON RIVER - Hermin Poedjiastoeti; Rosiana Indrawati (International Conference on Coastal and Delta Areas, 2015)
Babon River is one of the important rivers in Central Java through the Semarang Regency, Semarang City and Demak Regency. However, the amount of domestic, agricultural and industrial waste dumped into Babon River leads to increased pollution load and decrease in capacity. This study aimed to calculate the pollution load capacity using the Streeter Phelps method with appllied QUAL2Kw program to describing the quality of river water through the profiles of BOD, COD and TSS. And then it was compared with the standard stream due to Government Regulation No. 82/2001 about Management of Water Quality and Water Pollution Control. The study area includes Babon River from upstream to downstream that divided into 8 segments. The simulation BOD’s curve, COD’s curve and TSS’s curve results that maximum pollution load capacity of the Babon River for BOD and COD parameters contained in the segment 8 and the TSS parameter is in segment 2, while for the minimum pollution load capacity for BOD parameter contained in segment 1, COD in segment 6 and TSS in segment 7. The result of simulation due to pollution load capacity uses minimum flow rate is compared with Government Regulation No. 82/ 2001, it indicate that in segment 8 has no capacity for water quality standard class I, II and III with pollution load capacity of BOD ranged 24, 5 kg / day – 54,2 kg / day, and then the pollution load capacity of COD has exceeded the water quality standard class I of 42,1 kg / day, while pollution load capacity of TSS parameter meet the capacity of all classes.Keywords: Babon River, Pollution Load Capacity, Water Quality, QUAL2Kw